Low energy small solutions of systems of Kirchhoff-type equations on RN. Issue 3 (December 2019) - Zhou, Xingwei; Yao, Li
Low energy-induced vibration has been ignored, which, however, might lead to damage of a structure. The main purpose of this paper is to study the low energy small solution sequence of systems of Kirchhoff-type equations by the variational approaches. Our result shows that the low energy vibration can be controlled by setting the parameters and this can be used for optimization of structures under small perturbations, e.g. the bridge vibration under winds.